A brief history of the formation of a number of medical science branches and kinds of high-tech medical care for adult patients (review) - A. S. Kiselev (Сеченовский вестник, 2014)
The article investigates the formation and development of a number of leading medical fi elds. It focuses on high-tech scientifi c education sectors and types of care for adult patients.